2022
DOI: 10.3390/jcm11175167
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Diagnosis, Prevention, and Treatment of Cardiotoxicity in Cardio-Oncology

Abstract: Gender differences exist throughout the medical field and significant progress has been made in understanding the effects of gender in many aspects of healthcare. The field of cardio-oncology is diverse and dynamic with new oncologic and cardiovascular therapies approved each year; however, there is limited knowledge regarding the effects of gender within cardio-oncology, particularly the impact of gender on cardiotoxicities. The relationship between gender and cardio-oncology is unique in that gender likely a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 58 publications
(116 reference statements)
0
2
0
Order By: Relevance
“…A similar result of less importance on age and gender was mentioned by Kobat et al [ 13 ]. Other studies have found advanced age [ 14 ] and female sex [ 15 ] as risk factors for cardiotoxicities.…”
Section: Discussionmentioning
confidence: 99%
“…A similar result of less importance on age and gender was mentioned by Kobat et al [ 13 ]. Other studies have found advanced age [ 14 ] and female sex [ 15 ] as risk factors for cardiotoxicities.…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors predisposing patients to toxicity include genetic factors, female sex, cumulative dose, continuous infusions (as opposed to boluses), and combination therapy (Table 1) [28,31]. When treating patients undergoing therapy with anthracyclines, the PCP should monitor for cardiotoxicities with cardiac biomarkers (during therapy) and serial echocardiography (1, 3 or 5 years) for up to ten years [32].…”
Section: Anthracyclinesmentioning
confidence: 99%